CI-867, a new semisynthetic penicillin: in vitro studies. - Weaver, S S (1980)
CI-867, a new semisynthetic penicillin, has exhibited broad-spectrum activity in vitro against gram-positive cocci, except penicillin G-resistant Staphylococcus aureus, and against gram-negative bacilli. It was especially active against Pseudomonas aeruginosa and as active as mezlocillin and piperacillin against Klebsiella pneumoniae. CI-867 was bactericidal against most organisms. Its activity was greatly reduced when the inoculum was increased from 10(5) to 10(7) organisms per ml.